3D plotting of highly uniform Sr5(PO4)2SiO4 bioceramic scaffolds for bone tissue engineering. Issue 37 (7th September 2016) - Zhu, Huiying; Zhai, Dong; Lin, Chucheng; Zhang, Yali; Huan, Zhiguang; Chang, Jiang; Wu, Chengtie
Abstract : Novel bioactive ceramic scaffolds were 3D-plotted with controlled pore structures and the ions released from the scaffolds stimulated both osteogenesis and angiogenesis of tissue cells. Abstract : Bioceramics play an important role in bone regeneration. However, it is challenging to design bioceramic scaffolds with suitable ionic components and beneficial osteo/angio-stimulation ability for enhanced bone regeneration. In this study, we successfully synthesized a pure-phase Sr5 (PO4 )2 SiO4 (SPS) bioactive ceramic through a solid-state reaction method and further prepared highly uniform SPS bioceramic scaffolds with controlled macropore sizes and mechanical strength by a 3D-plotting technique, and the biological responses of rabbit bone marrow stromal cells (rBMSCs) and human umbilical vein endothelial cells (HUVECs) after culturing with different concentrations of SPS extracts and porous scaffolds were systematically studied. The results showed that the ionic products from SPS bioceramics significantly stimulated the proliferation, alkaline phosphate (ALP) activity and osteogenesis-related gene expression (Runx2, ALP, OCN, OPN) of rBMSCs as well as the proliferation and angiogenesis-related gene expression (VEGF, KDR, eNOS, HIF 1α) of HUVECs. 3D-plotted SPS scaffolds could effectively support the attachment and proliferation of both rBMSCs and HUVECs, and the proliferation rates of the two kinds of cells in SPS scaffolds were distinctively higher than those in β-tricalcium phosphate (β-TCP) scaffolds prepared by the same method. In addition, the compressive strength of SPS scaffolds could be well controlled in the range 8–30 MPa when their pore size varied from 100 to 300 μm, which was significantly higher than those of β-TCP scaffolds with similar pore sizes (∼1.5 times). Our results demonstrated that 3D-plotted SPS bioceramic scaffolds with such a specific ionic combination and high mechanical strength as well as good degradability possessed the ability to stimulate both osteogenic and angiogenic differentiation of tissue cells, indicating that they might be promising biomaterials for bone tissue engineering.